Survey on security threats in mobile cloud computing - Iniyan, S.; Senthilraja, M.; Srinivasan, R.; Palaniraj, A. (International Journal of Engineering and Technology, 2018)
Cell phones are turning into a basic piece of our day by day life because of most proficient and powerful specialized devices without time and space boundation. Everybody has a portable, tablet, tablet with calling office i.e. Fablet. Distributed computing (DC) has been broadly perceived as the cutting edge's registering foundation with the fast development of portable applications and the support of Cloud Computing for an assortment of administrations, the Mobile Cloud Computing (MCC) is presented as an incorporation of Cloud Computing into the Mobile Environment. Portable Cloud Computing is picking up stream. MCC is alluded to as the framework where both the information stockpiling and the information handling occur outside the cell phone. In MCC condition, Cloud Computing, Mobile Computing and Application confront a few difficulties like Mobile Computation Offloading, Seamless Connectivity, Vendor/Data Lock-in, Long WAN Latency, Live VM (Virtual Machine) relocation issues, Low Bandwidth, Energy-Efficient Transmissions and Trust-Security and Privacy Issues. In this paper, I have talked about around a few difficulties and issues identified with the Mobile Cloud Computing. This paper gives data about Mobile Cloud Computing Application, Security and Issues.